2003
DOI: 10.1128/jcm.41.1.192-196.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Massilia timonae and Massilia timonae -Like Isolates from Human Patients, with an Emended Description of the Species

Abstract: The description of Massilia timonae, a nonfermentative aerobic gram-negative rod, was based on a single strain. A subsequent report of a second isolate has been recently published. Phenotypic descriptions of these two strains were based primarily on commercial test kit results. We have identified three additional strains as M. timonae by 16S rRNA sequence analysis and have characterized them phenotypically in parallel with the type strain of M. timonae, CIP 105350, by conventional test methods. A fourth strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 12 publications
2
47
0
Order By: Relevance
“…C. gilardii is not known for its pathogenicity; however, it has been reported to infect humans, in one case causing fatal sepsis following the dissemination of an infection with intestinal focus (33). M. timonae has also been reported to infect humans, being isolated from blood, cerebrospinal fluid, and bone samples (36). Interestingly, Neisseriales were detected in 6 CD patients and in 1 control, the species detected being Eikenella corrodens (3 CD patients versus 0 controls) and an unclassified Vogesella species (3 CD patients versus 1 control).…”
Section: Resultsmentioning
confidence: 99%
“…C. gilardii is not known for its pathogenicity; however, it has been reported to infect humans, in one case causing fatal sepsis following the dissemination of an infection with intestinal focus (33). M. timonae has also been reported to infect humans, being isolated from blood, cerebrospinal fluid, and bone samples (36). Interestingly, Neisseriales were detected in 6 CD patients and in 1 control, the species detected being Eikenella corrodens (3 CD patients versus 0 controls) and an unclassified Vogesella species (3 CD patients versus 1 control).…”
Section: Resultsmentioning
confidence: 99%
“…Mycobacterium elephantis and Massilia timonae, which have been reported as human pathogens [10][11][12][13] , were found in sludge samples collected from tsunamiaffected areas (Table 5). The most probable reservoir of these bacteria is the outer environment, as we also identified Mycobacterium moriokaense in sample C-1 14) .…”
Section: Discussionmentioning
confidence: 99%
“…The relative values for bacterial genera are indicated by color intensity with the legend indicated at the top right corner been reported to utilize testosterone under both oxic and anoxic conditions. The genus Massilia was mainly isolated from the blood of an immunocompromised patient (Lindquist et al 2003) and has been recently found in environmental samples, such as soil samples from China and in the drinking water distribution system in Seville (Spain) (Gallego et al 2006;Wang et al 2012a). In this study area, Steroidobacter was found to closely relate to Cd content (R 2 =0.729, P<0.05), while Massilia had significant correlation with Cd and Cr contents (R 2 =0.718, P<0.05; R 2 =0.671, P<0.05).…”
Section: Bacteria With Potential Resistance To Heavy Metalsmentioning
confidence: 99%